2022
DOI: 10.1101/2022.03.17.22272446
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Founder effect contributes to the unique pattern of SARS-CoV-2 variant B.1.1.519 emergence in Alaska

Abstract: Alaska is the largest geographic state in the United States with the lowest population density and a mix of urban centers and isolated rural communities. The differences in population dynamics in Alaska from the contiguous United States may have contributed to a unique pattern of emergence and spread of SARS-CoV-2 variants observed in early 2021. Here we examined 2,323 virus genomes from Alaska and 278,635 virus genomes from the contiguous United States collected between the first week of December 2020 through… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This was suggested because of the inconclusive results over the positive selection of those mutations and coinciding timing with the nexus of dispersal from Asia to Europe associated with the D614G mutation (Grubaugh et al, 2020). Given the emergence of other lineages in the Lower 48 even though BA.2.3 was detected around the same time for many locations, Alaska’s emergence of BA.2.3, and B.1.1.519 earlier in the pandemic, implicates repeat occurrences of variant emergence influenced by the founder effect (Haan et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This was suggested because of the inconclusive results over the positive selection of those mutations and coinciding timing with the nexus of dispersal from Asia to Europe associated with the D614G mutation (Grubaugh et al, 2020). Given the emergence of other lineages in the Lower 48 even though BA.2.3 was detected around the same time for many locations, Alaska’s emergence of BA.2.3, and B.1.1.519 earlier in the pandemic, implicates repeat occurrences of variant emergence influenced by the founder effect (Haan et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…During this wave, the Alpha variant (lineage B.1.1.7; Rambaut et al, 2020), which showed evidence of increased transmissibility, became the most prevalent variant for most places globally (Volz et al, 2021). Unlike other regions, including within the contiguous 48 states of the United States (hereafter referred to as Lower 48), Alaska’s dominant lineage was B.1.1.519 throughout early 2021, which was similar to Mexico in late 2020 (Haan et al, 2022; Rodríguez-Maldonado et al, 2021). The timeline in which Alpha and B.1.1.519 emerged in Alaska paired with the striking difference in prevalence between Alaska, which had a peak B.1.1.519 prevalence of 77.9%, and the Lower 48, which had a peak prevalence of 4.9%, was indicative of a B.1.1.519 founder event in Alaska (Haan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations